The myriad of nephritis in levamisole-adulterated cocaine vasculopathy (2018)
ABSTRACT: Background: Up to 88% of cocaine is tainted with levamisole, an anthelmintic withdrawn from the market due to toxicity. Since 2010 levamisole-adulterated cocaine vasculopathy (LACIV) patients, characterised by retiform purpura, ear necrosis, multisystemic compromise and positivity for multiple autoantibodies, have been reported. Renal involvement is the most serious and heterogeneous manifestation. Objectives: To describe the renal involvement of patients with LACIV. Methods: We describe the renal manifestations of 30 patients with LACIV evaluated from December 2010 to May 2017. Results: All patients were mestizo, median age of 31 (IQR 27–38), male:female ratio 5:1, time from symptoms to diagnosis 12 months (IQR 6–24). Nephritis found in 57%, creatinine elevation in 40%, median 1.85 mg/dl (IQR 1.2–4.0), 70% had proteinuria, median 3184 mg/day (IQR 552–5100), 58% in nephrotic-range; 88% had hematuria and 41% pyuria and cilindruria. Biopsy was performed in 7 patients (41%), showing immune complex mediated extracapillary glomerulonephritis (29%), membranous glomerulonephritis (29%), pauci-immune proliferative glomerulonephritis (14%), focal and segmental glomerulosclerosis (14%) and C3 mediated extracapillary glomerulonephritis (14%) (image). Three patients (10%) developed end-stage kidney disease. Image: A. Membranous glomerulonephritis: HE: glomerular thickened capillary walls, mild mesangial cellularity increase. B. GMS: capillary wall thickening and spikes (arrow). C. DIF: strong and diffuse IgG deposits on capillary walls. D. Immune complex mediated Extracapillary Focal Necrotizing Glomerulonephritis: HE: endocapillary proliferation, epithelial crescent (arrow). E. GMS: capillary wall rupture next to the crescent (arrow). F. DIF: Mesangial strong and diffuse IgG deposits. G. C3 mediated extracapillary glomerulonephritis: HE: glomerular capillary narrowing, epithelial crescent (arrow). H. GMS: normal capillary networks, epithelial crescent (arrow). I. DIF: C3 strong and diffuse positivity. J. Pauci-immune proliferative glomerulonephritis: PAS: epithelial crescents (arrows and asterisk). K. Trichrome: epithelial crescent (arrow). L. DIF for C3: weak deposits on capillary tuft. Non-immune complexes. M. Focal and segmental glomerulosclerosis: HE: segmental sclerosing lesions (arrow). N. PAS: segmental sclerosing lesions (asterisks). O. DIF for IgM: nonspecific positivity on a sclerotic segment. Conclusions: Although skin manifestations are the most characteristic and prevalent features in LIVEN, renal involvement is frequent, clinically and histologically heterogeneous, and potentially serious. The great heterogeneity on the histopathological findings suggests the participation of different physio-pathological mechanisms, establishing renal biopsy as necessary to identify the type of nephropathy and thus, optimal guidance of therapy.